Joining the Dots: Threads of Connection in Cam and the Bird-People (The Author’s Journey) - de Roo, Elena (Auckland University of Technology, 2019)
Exegesis Joining the Dots: Threads of Connection in Cam and the Bird-people (The Author’s Journey), discusses the author’s motivation for writing a middle-grade fantasy novel and examines selected elements of connection within Cam and the Bird-People. Thesis Cam and the Bird-people is a children’s fantasy novel aimed at 9-12 year olds. When twelve-year-old Cam finds a photo of Theo, the father she’s never met — a photo her mother swore didn’t exist — her life is turned upside down. In the heat of the moment, she decides to visit the art gallery, the last place her father was seen. There, she is introduced to The Fall of Icarus (Hammond, 1995), the painting Theo was writing his thesis on. Events take a turn for the worse, when, once alone with the painting, Cam is sucked without any warning, through the canvas and into the strange world of the bird-people and the sub-gallery. With the help of Timo (a portrait come to life) and Lila (Cam’s bossy mirror image) Cam sets out through The Door of No Return to find her father. But first, she and her friends, must journey to the deepest and darkest levels of the sub-gallery to defeat the Curator — the cold-hearted collector, who would like nothing better than to add a new specimen to his cabinets full of stuffed creatures.
Keywords: New Zealand children's literature; Creative writing; Middle grade; Portal fantasy